9th Workshop on Cloud Technologies in Education: Report - Arnold E. Kiv; Serhiy O. Semerikov; Mariya P. Shyshkina; Andrii M. Striuk; Mykola I. Striuk; Yuliia V. Yechkalo; Iryna S. Mintii; Pavlo P. Nechypurenko; Olga O. Kalinichenko; Larisa S. Kolgatina; Kateryna V. Vlasenko; Svitlana M. Amelina; et al. (Academy of Cognitive and Natural Sciences, 2022)
This is an introductory text to a collection of selected papers from the 9th Workshop on Cloud Technologies in Education (CTE 2021) which held in Kryvyi Rih, Ukraine, on the December 17, 2021. It consists of short introduction, papers' review and some observations about the event and its future.